Scientiﬁc Medical Library’s objective is the extension access to information of medical proﬁle (Confluenţe Bibliologice, 2012)
The free exchange of scientiﬁc and medical information can play an important role in developing of the country. Access to information is critical to advancing science and promoting healthy people and knowledge is indispensable in making informed decisions in health care, education, and research. As new models of scholarly communication emerge, the Scientiﬁc Medical Library has responded by developing and supporting new methods of providing access to information and by creating new publishing support services. The Library started to create an Institutional Repository designed to capture the scholarly output of the State Medical and Pharmaceutical University „Nicolae Testemitanu” of Moldova and to maximize the research impact of this output. The Scientiﬁc Medical Library has been key player in promoting, developing and supporting open access publishing initiatives and services in medical higher education and for whole medical community of Republic of Moldova.
Keywords: institutional repositories; open access; information and research activity